A new frog of the genus Hylodes (Amphibia : Leptodactylidae) from Minas Gerais, Brazil - Nascimento, L. B.; Pombal, J. P.; Haddad, CFB (Cambridge University Press, 2001)
A new species of leptodactylid frog is described from Parque das Mangabeiras, in Belo Horizonte, Minas Gerais, south-eastern Brazil. The new species is a member of the Hylodes lateristrigatus group, and is characterized by medium size, snout rounded in dorsal view and protruding in lateral view, presence of vocal slits and sacs, upper surface of finger and toe discs with well-developed scutes, a weakly developed stripe on the upper lip, dorsum, arm, leg, and foot dark brown with small irregular brown and black dots, and absence of red and yellow spots in live specimens. The descriptions of the tadpoles and vocalizations, and information on natural history are provided. Hylodes perplicatus (Miranda-Ribeiro), previously considered a member of the H. nasus species group, is transferred to the H. lateristrigatus species group.
Keywords: Amphibia; Anura; Leptodactylidae; Hylodinae; Hylodes uai sp nov.; advertisement call; tadpole; south-eastern Brazil